Obesity, multiple chronic conditions, and the relationship with physical function: Data from the national health and aging trends survey. (April 2023) - Shirazi, Daniela; Haudenschild, Christian; Lynch, David H.; Fanous, Marco; Kahkoska, Anna R.; Jimenez, Daniel; Spangler, Hillary; Driesse, Tiffany; Batsis, John A.
Highlights: What is already known on this topic: Both obesity and multiple chronic conditions are public health concerns with rates rising in older adult populations leading to increased risk of adverse events. Few studies have evaluated the implications of both on physical function in persons with obesity. What this study adds: This epidemiological study highlights the importance of co-existing obesity and multiple chronic conditions in older adults. Rates of concurrent obesity and multiple chronic conditions are high, as are the rates of functional limitations and risk of frailty, compared to those without obesity. How this study might affect research, practice or policy: The relationship of obesity and multiple chronic conditions, with frailty and physical limitations signifies the importance of developing interventions in this subgroup. Abstract: Background: The population of older adults living with multiple chronic conditions (MCC) continues to grow. MCC is independently associated with functional limitation and obesity. The aim of our study was to evaluate the association between obesity and MCC, and secondarily, the combined presence of obesity and functional limitations with MCC. Methods: We analyzed cross-sectional survey data from the National Health and Aging Trends Survey (NHATS) 2011 baseline data, a nationally representative Medicare beneficiary cohort of adults in the United States. We evaluated the coexistent prevalence of obesity and MCC overall, and by standard body mass index (BMI) categories. We then evaluated the prevalence of functional limitations (mobility, self-care, and household activities) and Fried-defined frailty status in persons with a BMI ≥ 30 kg/m 2 . Logistic regression was used to measure the association between MCC and BMI, and functional limitations and MCC among those with obesity. Results: In the 6, 600 participants, the prevalence of concurrent obesity and MCC was 30.4%. Of those with obesity, the prevalence of MCC was 84.0%, and were more likely to have MCC (adjusted OR: 2.17, 95% CI 1.86, 2.54) compared to a normal BMI. Obesity and functional limitations or frailty were more likely have MCC than individuals with obesity alone. Conclusions: We found that individuals with obesity is strongly associated with MCC and that functional limitations and frailty status have a greater association with having MCC than individuals with obesity without MCC. Future longitudinal analyses are needed to ascertain this relationship.